2019
DOI: 10.3390/biom9090417
|View full text |Cite
|
Sign up to set email alerts
|

System Analysis of MIRNAs in Maize Internode Elongation

Abstract: MicroRNAs (miRNAs), the post-transcriptional gene regulators, are known to play an important role in plant development. The identification of differentially expressed miRNAs could better help us understand the post-transcriptional regulation that occurs during maize internode elongation. Accordingly, we compared the expression of MIRNAs between fixed internode and elongation internode samples and classified six differentially expressed MIRNAs as internode elongation-responsive miRNAs including zma-MIR160c, zma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
(81 reference statements)
1
10
0
Order By: Relevance
“…(10.25), and miR396f (6.34) in deepwater stress treatment (Peng et al, 2019). Similar to miRNAs in the internode, the expression of some conserved miRNAs such as miR166, miR167, and miR171 in our study was similar to previous reports in maize and cucumber (Xu et al, 2019;Zhang et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…(10.25), and miR396f (6.34) in deepwater stress treatment (Peng et al, 2019). Similar to miRNAs in the internode, the expression of some conserved miRNAs such as miR166, miR167, and miR171 in our study was similar to previous reports in maize and cucumber (Xu et al, 2019;Zhang et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…These results show the specificity of miRNAs even in the same miRNAs families. Members of miRNAs such as miR159, miR164, miR167, miR172, and miR396 were previously reported in maize on internode elongation (Peng et al, 2019). In our study, we also found a similar expression pattern of these miRNAs such as miR159a (7.49), miR164c (8.82), miR167c (−1.32), miR172d (10.25), and miR396f (6.34) in deepwater stress treatment (Peng et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lignin in higher plants is synthesized via the phenylpropanoide pathway and the lignin-specific pathway, and phenylalanine is synthesized via a series of reactions to produce 3 major lignin monomers, which are ultimately polymerized into polymeric lignin under the catalysis of peroxidase (POX) and laccase (LAC) [ 9 ]. Numerous studies showed that various non-coding RNAs, such as miR156, miR160, miR164, miR319, and miR397, target LAC [ 50 , 51 , 52 ]. The present study found that novel_57 and novel_104 directly targeted LAC to prevent individual lignin monomers from entering the lignin synthesis pathway ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, increases in plant height must have to deal with stem lodging losses. Stem lodging, caused by the bending or breaking of the stalk, is greatly impacted by stalk strength and stem morphological traits, therefore it could be said that maize stem strength impacts both grain yield and silage quality 10,13,14 .…”
Section: Introductionmentioning
confidence: 99%